Chitosan Fibers Modified with HAp/β–TCP Nanoparticles - Dariusz Wawro; Luciano Pighinelli (International Journal of Molecular Sciences, 2011)
This paper describes a method for preparing chitosan fibers modified with hydroxyapatite (HAp), tricalcium phosphate (β-TCP), and HAp/β-TCP nanoparticles. Fiber-grade chitosan derived from the northern shrimp (Pandalus borealis) and nanoparticles of tricalcium phosphate (β-TCP) and hydroxyapatite (HAp) suspended in a diluted chitosan solution were used in the investigation. Diluted chitosan solution containing nanoparticles of Hap/β-TCP was introduced to a 5.16 wt% solution of chitosan in 3.0 wt% acetic acid. The properties of the spinning solutions were examined. Chitosan fibers modified with nanoparticles of HAp/β-TCP were characterized by a level of tenacity and calcium content one hundred times higher than that of regular chitosan fibers.